Myomectomy in Early Pregnancy - A Case Report - Santos, L (2006)
Uterine leiomyomas are by far the most common benign tumours of the female genital tract. The true incidence of leiomyomas during pregnancy is, however, unknown. Although leiomyomas usually remain asymptomatic during pregnancy, they may complicate its course. The management of leiomyoma during pregnancy is medical, but, in rare circumstances, surgical intervention and myomectomy may be required. A case of myomectomy in early pregnancy is described.